Peran Strategis Relawan TRC BPBD Kota Salatiga dalam Penanggulangan Bencana Tanah Longsor di Kota Salatiga - Catur, Enggal Junian Bagas; Utomo, Alvianto Wahyudi; Siahainenia, Wacana Royke Roberth (Innovative: Journal Of Social Science Research, 2025)
The strategic role of TRC BPBD (Regional Disaster Management Agency) volunteers plays a key part in managing the landslide disaster risk in the Salatiga area, as well as the efforts made by BPBD to enhance the strategic role of volunteers. The aim of this study is to outline the background of the issues related to the role of BPBD volunteers in handling landslide disasters, as well as the efforts made by BPBD Salatiga to strengthen the volunteers' contributions in disaster management. This research adopts a qualitative approach with data collection methods through interviews and questionnaires. Role theory, particularly the Prescribed Role dimension, is applied to analyze the data obtained. The findings reveal that the role of TRC BPBD volunteers in Salatiga plays a crucial part in landslide disaster management, especially in preparedness, emergency response, and post-disaster recovery. Although volunteers have a critical role, BPBD Salatiga needs to continuously improve training, coordination, and the resources that support the performance of TRC volunteers.